# Integral of (x-100)(.002e^(-.002*x))

## Homework Statement

find the integral from 100 to infiniti for (x-100)(.002e^(-.002*x))

## The Attempt at a Solution

.(xe^-(.002x))(e^(-.002x))-(-100e^(-.002x)) |from 100 to infiniti = -(100e^-.2)(e^-.2)+100e^(-.2)=14.84

Related Calculus and Beyond Homework Help News on Phys.org
vela
Staff Emeritus
Homework Helper

You didn't integrate it correctly. Post the details of your calculations so we can see where you went wrong.

(x-100)(.002e^(-.002*x))
I first multiplied out these two and got .002xe^(-.002x) - .2e^(-.002x). Then integrating the .002xe^(-.002x) I integrated the e part first and then the x part to get -xe^(-.002x) * e^(-.002x) and then I integrated the .2e^(-.002x) and got -100e^(-.002x).

vela
Staff Emeritus
Homework Helper

The first integral you did is wrong. You need to do it by parts.

.002xe^(-.002x) - .2e^(-.002x). Ok. u=.002x du=dx
v= -(1/.002)e^(-.002x) dv=e^(-.002x)
so then, (.oo2x)(-(1/.002)e^(-.002x)- Integral of -(1/.002)e^(-.002x) dx from 100 to infiniti. (.oo2x)(-(1/.002)e^(-.002x) + (1/(.002*.002))e^(-.002x) from 100 to infiniti
0 - .2*(-409.3654)+(204682.69)==way wrong answer...Oh my goodness this is the ultimate in frustration...

vela
Staff Emeritus
Homework Helper

Reformatted a bit to make it easier to read.
0.002 x e^(-0.002x) - 0.2 e^(-0.002x)

u = 0.002x
du = dx
That's wrong. Fix this and the value for the first integral should come out okay.
dv = e^(-0.002x) dx
v = -(1/0.002) e^(-0.002x)

so then,

(0.002x)(-(1/0.002) e^(-0.002x) - Integral of -(1/0.002)e^(-0.002x) dx from 100 to infinity.
(0.002x)(-(1/0.002) e^(-0.002x) + (1/(0.002*0.002)) e^(-0.002x) from 100 to infinity
[0 - 0.2*(-409.3654)] + (204682.69) == way wrong answer

Oh my goodness this is the ultimate in frustration...
This is only the value of the first integral. You still need to do the integral of 0.2 e^(-0.002x).